Stromal PLAU mediates tumor progression and informs a novel therapeutic target in triple-negative breast cancer - Jun Zou; Jingyao Zhang; Yu Li; Baowen Yuan; Yuanyi Wang; Yalong Qi; Qian Wang; Wan Qin; Xianglin Yuan; Binghe Xu (Cancer Cell International)
Abstract Triple-negative breast cancer (TNBC) is an aggressive subtype characterized by limited treatment options and poor prognosis. Recent evidence highlights the crucial role of cancer-associated fibroblasts (CAFs) in TNBC progression, yet their molecular characteristics remain incompletely understood. In this study, we performed a comprehensive analysis combining bioinformatics approaches with experimental validation to investigate CAF-related genes in TNBC. Using weighted gene co-expression network analysis (WGCNA) of TNBC samples from TCGA and METABRIC datasets, we identified 185 CAF-related genes significantly associated with extracellular matrix organization and TGF-β signaling pathways. Through rigorous statistical modeling, we developed a 3-gene prognostic signature (CERCAM, JAM3, PLAU) that effectively stratified TNBC patients into high- and low-risk groups with distinct survival outcomes. Importantly, we validated the functional role of PLAU, one of the signature genes, through in vitro and in vivo experiments. Results showed that CAF-derived PLAU played key role in the malignant behaviors of TNBC. Our findings provide new insights into CAF-mediated TNBC progression and suggest potential stromal targets for therapeutic intervention.